APAKAH PENDEKATAN FRAUD TRIANGLE EFEKTIF UNTUK MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Soni Agus Irwandi; Diyah Pujiati; Winda Dwi Rahmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze fraudulent actions in financial statements by using the Fraud Triangle theory approach. By using quantitative methods using secondary data. The population in this study are mining companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling technique was done by purposive sampling to produce 145 samples. In this study, the technical analysis model uses path analysis and SPSS version 26. The independent variables in this study are financial stability as measured by the asset change proxy (Achange), financial targets as measured by the return on assets (ROA) proxy, the nature of the industry as measured by proxy inventory and financial statement fraud as measured by the Beneish M-Score model with a dummy variable. The results of this study indicate that financial stability has a significant effect on financial statement fraud. However, financial targets, nature of industry and rationalization were not found to have an effect on fraudulent financial statements.